Formulation and Antibacterial Activity Testing of Acne Patch Containing Mangrove Leaf Extract (Sonneratia alba) Against Staphylococcus aureus - Dwi Azziatus Silfia; Dzun Haryadi Ittiqo; Melati Permata Hati; Yuli Fitriani (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2026)
Indonesia has significant potential in the utilization of biological natural resources, including mangrove plants known to contain bioactive compounds with pharmacological value. One mangrove species, Sonneratia alba, contains flavonoids, alkaloids, and steroids that exhibit potential as natural antibacterial agents. This study aimed to develop an acne patch formulation based on Sonneratia alba leaf extract and to evaluate its physical characteristics and antibacterial activity against Staphylococcus aureus. The study employed an experimental laboratory design with extract concentrations of 5% (F1), 7.5% (F2), and 10% (F3), along with a negative control (F0) and a positive control (pure extract). Physical evaluations included organoleptic properties, pH, weight uniformity, thickness, folding endurance, elongation, and moisture content. Antibacterial activity was assessed using the agar diffusion method. The results showed that all formulations met the required physical quality parameters, and formulation F3 (10%) produced the largest inhibition zone against Staphylococcus aureus, measuring 18.5 ± 0.58 mm, which is categorized as strong antibacterial activity. In conclusion, Sonneratia alba leaf extract demonstrates potential as a natural active ingredient in topical acne patch formulations. Further studies are recommended, including stability testing, skin irritation assessment, and quantitative analysis of active compounds using analytical techniques such as HPLC to ensure the safety and efficacy of the formulation.